Test The Wound Healing Activity Of Nephelium Lappaceium Fructus Cortex Extract Ointment On New Zealand Rabbits - Arif Wijayanto; Luluk Aniqoh Meliana Putri; Juvita Herdianty (Strada Journal of Pharmacy, 2022)
Nephelium lappaceium Linn.(Rambutan) is a natural ingredient rich in active substances that are beneficial to human health. In this study, the use of Nephelium lappaceium fructus cortex was used for the healing of open wounds where Nephelium lappaceium fructus cortex contains tannins which are expected to help heal open wounds. The content test was carried out using the phytochemical screening method of Nephelium lappaceium fructus cortex extract which showed the presence of alkaloids, flavonoids, saponins, and tannins, then a wound healing test was carried out with Nephelium lappaceium fructus cortex extract which was divided into 5 groups randomly, namely normal, negative control (Vaseline album) , positive control (Betadine salp® each gram contains 10% Povidone Iodine), presented topically 7.5% and 15% Nephelium lappaceium fructus cortex extract ointment. The back skin of New Zealand rabbits is 3-5 months old, weighs 1500–2000grams, has normal and healthy activities and has agile activities, is normal and in healthy condition, then was injured with a punch biopsy with a diameter of 5 mm, a depth of ± 0.5 mm, then treatment according to the test group for 21 days. Parameters measured included wound diameter in rabbits. The results showed that the ointment extract of Nephelium lappaceium fructus cortex 15% had an open wound healing activity which was comparable to a positive control with an open wound healing activity of 0.2mm.